Supercritical Carbon Dioxie; An Efficient Solvent for Herbal Extraction - Mohsen Dashtianeh Dashtianeh; Alireza Vatanara; Shamsali Rezazadeh (Institue of Medicinal Plants, ACECR, 2017)
Supercritical fluid extraction (SFE) is an alternative to liquid extraction using solvents. Supercritical fluids can have solvating powers similar to organic solvents, but with higher diffusivities, lower viscosity, and lower surface tension. Carbon dioxide is the most commonly used supercritical fluid owing to its nontoxic, nonflammable, inexpensive, environmental friendly properties and mild critical conditions (Tc = 31.1 ̊ C and Pc = 73.8 bar). Due to the low heat of process and the relatively unreactive solvent used in the extraction, the fragrant compounds derived often closely resemble the original characteristics of the raw material. Like solvent extraction,  extracts a wide range of compounds and leaves the aromatics unaltered by heat, rendering an essence more faithful to the original. In this review, some aspects of this etraction methods have been discussed.